Histological findings of experimental Streptococcus agalactiae infecion in nile tilapias (Oreochromis niloticus) - Inocente Filho, Clóvis; Müller, Ernst E.; Pretto-Giordano, Lucienne G.; Bracarense, Ana Paula F. R. L. (Brazilian Journal of Veterinary Pathology, 2009)
Nile tilapias (Oreochromis niloticus) were intraperitoneally infected with a Streptococcus agalactiae suspension containing 105CFU/mL. The strain of S. agalactiae used to experimental infection was isolated from naturally infected tilapias from Paraná, south Brazil. Fishes were kept in laboratory aquaria with adequate limnologic parameters, being euthanized 3, 7, 14, 21 and 28 days post-inoculation. The isolate caused exophtalmia, ocular opacity, erratic swimming, lethargy and darkness of the skin 3, 7 and 14 post-inoculation. Histopathology revealed a septicemia with a severe mononuclear infiltrate in meninges, epicardium and eyes. Inflammation occurred mainly 3 and 7 days post-inoculation, and at 21 and 28 days was not observed. A significant association was verified between infection with S. agalactiae and the presence of melanomacrophages centers in the liver and spleen. S. agalactiae was reisolated from brain and kidney 3, 7 and 14 days post-inoculation.